(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
One of the most important problems of the Railway Operations is the wear problems that occur in the rails under load and momentum. Many businesses in the world have developed different solution methods on this issue and the same methods are still applied. Noise is also the bleeding wound of many railway operators, regardless of or dependent on wear and fatigue problems. Noise, especially in the curves, adversely affects human and environmental health. In this report, we will examine the factors caused by these 2 problems and examine the solution methods with their costs.